PERSONAL BRANDING MAHASISWA GENERASI-Z Analisis Dramaturgi Pada Mahasiswa Universitas Langlangbuana Pengguna Instagram - Diana Aulia Fitri; Veny Purba; Dudi Yudha Kusuma (IKRAITH-EKONOMIKA, 2026)
This study aims to understand how Generation Z students at Langlangbuana University build and manage personal branding on Instagram through front-stage and back-stage management. The development of social media has changed the way individuals display their identities, with Instagram becoming a digital public space that allows students to strategically construct their self-image. This phenomenon demonstrates a duality between the ideal identity displayed in the public space and the more private everyday identity. This study uses a qualitative approach with descriptive methods to deeply explore the communication process, impression management strategies, and the dynamics of interactions between students and followers in personal branding practices. The theoretical basis of this study uses Erving Goffman's Dramaturgy Theory, which views social life as a performance, where individuals act as actors who manage impressions in front of the audience. The concept of front-stage and back-stage is used to analyze how students display their self-image through visual content, captions, and public interactions on Instagram, as well as how they reflect, plan, and self-control in the private space before publishing content. The research data were obtained through in-depth interviews and observations of Generation Z students who are active Instagram users. The results of this study are expected to provide an understanding of interpersonal communication strategies in the context of digital personal branding, while also revealing the dynamics between the demands of existence, image consistency, and the need for self-authenticity. Academically, this study contributes to the development of digital communication and personal branding studies, while practically it provides an overview for Generation Z students in managing their self-image consciously, strategically, and sustainably on social media.